Are MSMEs the Key to Poverty Reduction? Dynamic Evidence from Indonesia Utilizing ARDL Analysis - Azhari Azhari; Musrizal Musrizal; Win Konadi (Jurnal Ekonomi Kuantitatif Terapan, 2025)
This study aims to analyze the impact of MSMEs on poverty alleviation in Indonesia utilizing ARDL approach. The independent variables examined include the quantity of MSMEs, labor, and investment, with poverty serving as the dependent variable. Data spanning from 1990 to 2023 were employed for this analysis. The findings indicate that the number of MSMEs exerts no influence on poverty levels in either the short or long term. Conversely, the MSMEs workforce demonstrates a positive effect on poverty reduction in the short term, while investment yields a more substantial impact in the long term. Given the heterogeneity in poverty levels and MSME development across different regions in Indonesia, it is essential to consider regional variables when assessing the impact of MSMEs. Adopting a more region-specific approach will enable policies to better address the specific needs and challenges encountered by each region, thereby providing a fertile ground for future research.